Aerogel blanket

CN122940435APending Publication Date: 2026-10-20LG CHEM LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611133556.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-07-09
Filing Date
2020-09-01
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0009]然而,由于通过表面改性步骤的表面改性反应从气凝胶的最外部开始,因此,存在难以将足够量的表面改性剂引入到气凝胶内部的问题

Benefits of technology

[0020]根据本发明的气凝胶毡具有优异的长期防水性,因此,即使在会引起长时间暴露于水分中的苛刻条件下也可以保持其绝热性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_6
    Figure SMS_6
  • Figure SMS_7
    Figure SMS_7
Patent Text Reader

Abstract

This invention relates to an aerogel felt that has a 28-day water immersion rate (MIR-28D) of less than 100% by weight, calculated using Equation 1 below: [Equation 1] 28-day water immersion rate (MIR-28D, wt%) = {(weight of aerogel felt after immersion in distilled water at 21±2°C for 28 days - weight of aerogel felt before immersion in distilled water) / weight of aerogel felt before immersion in distilled water} × 100. The aerogel felt of this invention exhibits excellent long-term water resistance and maintains its thermal insulation properties even under harsh conditions that would lead to prolonged exposure to moisture.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The international application number of the original application is PCT / KR2020 / 011710, the international application date is September 1, 2020, the Chinese national application number is 202080006923.1, the date of entry into China is June 10, 2021, and the invention title is "Aerogel Felt".

[0002] Cross-references to related applications

[0003] This application claims the benefits of four patent applications filed with the Korean Intellectual Property Office on September 3, 2019: Korean Patent Application No. 10-2019-0109158, filed with the Korean Intellectual Property Office on September 30, 2019; Korean Patent Application No. 10-2019-0121123, filed with the Korean Intellectual Property Office on September 30, 2019; Korean Patent Application No. 10-2019-0121147, filed with the Korean Intellectual Property Office on September 30, 2019; and Korean Patent Application No. 10-2020-0084763, filed with the Korean Intellectual Property Office on July 9, 2020. The disclosures of these four patent applications are incorporated herein by reference in their entirety. Technical Field

[0004] The present invention relates to an aerogel felt that has excellent long-term waterproof properties and thus maintains its thermal insulation properties even under harsh conditions that would cause prolonged exposure to moisture. Background Technology

[0005] Aerogels are ultraporous materials with a porosity of approximately 90% to 99.9% and a pore size ranging from 1 nm to 100 nm, exhibiting high specific surface area (≥500 m²). 2 Aerogel materials ( / g) possess excellent properties such as ultralight weight, superior thermal insulation, and ultralow dielectric strength. Therefore, research is actively underway to develop aerogel materials and explore their practical applications as environmentally friendly high-temperature insulation materials, ultralow dielectric films for highly integrated devices, catalysts and catalyst supports, electrodes for supercapacitors, and electrode materials for seawater desalination.

[0006] The greatest advantage of aerogel is that it exhibits super insulation properties with a thermal conductivity of less than 0.300 W / mK, which is lower than that of conventional organic insulation materials such as polystyrene foam. It can also solve the fatal weaknesses of organic insulation materials, such as flammability and the generation of harmful gases in the event of a fire.

[0007] Typically, aerogels are prepared by the following method: preparing hydrogels from silica precursors such as water glass and alkoxysilanes (TEOS, TMOS, MTMS, etc.), and removing the liquid components inside the hydrogel without damaging the microstructure.

[0008] In particular, hydrophobic silica aerogel felt, which forms a hydrophobic silica aerogel within fibers, is a functional thermal insulation material that prevents moisture corrosion and is widely used in construction and industrial applications. Typically, this hydrophobic silica aerogel felt is manufactured through steps including silica sol solution preparation, gelation, aging, surface modification, and drying.

[0009] However, since the surface modification reaction begins at the outermost edge of the aerogel, it is difficult to introduce a sufficient amount of surface modifier into the interior of the aerogel. Under harsh conditions of prolonged exposure to moisture, the aerogel eventually permeates into its interior, leading to a deterioration in its thermal insulation properties. This, in turn, causes water adsorption due to hydrogen bonds between hydroxyl groups on the surface of the aerogel and water, further degrading the aerogel's durability.

[0010] [Existing technical documents]

[0011] [Patent Literature]

[0012] (Patent Document 1) KR10-2012-0070948A Summary of the Invention

[0013] Technical issues

[0014] One aspect of the present invention provides an aerogel felt that has excellent long-term water resistance and thus maintains its thermal insulation properties even under harsh conditions that would cause prolonged exposure to moisture, in order to prevent corrosion under insulation (CUI) of the aerogel.

[0015] Technical solution

[0016] According to one aspect of the invention, an aerogel felt is provided, wherein the 28-day moisture impregnation rate (MIR-28D) calculated by Equation 1 below is less than 100% by weight.

[0017] [Equation 1]

[0018] 28-day moisture impregnation rate (MIR-28D, weight %) = {(weight of aerogel mat after 28 days of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water} × 100

[0019] Beneficial effects

[0020] The aerogel felt according to the invention has excellent long-term waterproof properties, and therefore can maintain its thermal insulation properties even under harsh conditions that would cause prolonged exposure to moisture. Attached Figure Description

[0021] The accompanying drawings illustrate preferred embodiments of the invention by way of example and, together with the detailed description of the invention given below, are intended to enable a further understanding of the technical concept of the invention. Therefore, the invention should not be understood solely based on the matters shown in these drawings.

[0022] Figure 1 This is a perspective view of an aerogel felt manufacturing apparatus illustrating a second aspect of a method for manufacturing aerogel felt according to an embodiment of the present invention. Detailed Implementation

[0023] The invention will now be described in more detail to aid in understanding it.

[0024] It should be understood that the words or terms used in the specification and claims of this invention should not be construed as having meanings limited to those defined in common dictionaries. It should also be understood that, based on the principle that the inventors can appropriately define the meanings of words or terms to best illustrate the invention, the words or terms are to be understood to have meanings consistent with their meanings in the context of the relevant art and in the technical concept of the invention.

[0025] In this invention, "long-term water resistance" refers to the water resistance determined by the weight increase of the aerogel felt due to water absorption when exposed to a humid environment for an extended period. "Long-term" can refer to a time greater than 7 days (168 hours; 1 week), and can specifically refer to 28 days (672 hours; 4 weeks) as defined in ISO:16535 (Thermal insulating products for building applications - Determination of long-term water absorption by immersion; Method 2: total immersion). Therefore, in this invention, the water resistance determined by the weight increase of the aerogel felt due to water absorption when exposed to a humid environment for an extended period is represented by the 28-day water immersion rate (MIR-28D) calculated using Equation 1 below, and a lower 28-day water immersion rate indicates better long-term water resistance.

[0026] [Equation 1]

[0027] 28-day moisture impregnation rate (MIR-28D, weight %) = {(weight of aerogel mat after 28 days of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water} × 100

[0028] Furthermore, the "intermediate water resistance" defined in this invention refers to the water resistance determined by the increase in weight due to water absorption by the aerogel felt when exposed to a humid environment for an intermediate period of time. "Intermediate" can refer to a time shorter than 7 days (168 hours; 1 week), and can specifically refer to 96 hours (4 days) as defined in ASTM C1104 (Standard Test Method for Determining the Water Vapor Sorption of Unfaced Mineral Fiber Insulation). Therefore, in this invention, the water resistance determined by the increase in weight due to water absorption by the aerogel felt when exposed to a humid environment for an intermediate period of time is expressed by the 96-hour water immersion rate (MIR-96H) calculated using Equation 2 below, and a lower 96-hour water immersion rate indicates better intermediate water resistance.

[0029] [Equation 2]

[0030] 96-hour moisture impregnation rate (MIR-96H, weight %) = {(weight of aerogel mat after 96 hours of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water} × 100

[0031] Furthermore, the "short-term water resistance" defined in this invention refers to the water resistance determined by the increase in weight due to water absorption by the aerogel felt when exposed to a humid environment for a short period of time. "Short-term" can refer to a time shorter than 1 day (24 hours), and can specifically refer to 15 minutes (1 / 4 hour) as defined in ASTM C1511 (Standard Test Method for Determining the Water Retention (Repellency) Characteristics of Fibrous Glass Insulation). Therefore, in this invention, the water resistance determined by the increase in weight due to water absorption by the aerogel felt when exposed to a humid environment for a short period of time is expressed by the 15-minute water immersion rate (MIR-15M) calculated using Equation 3 below, and the lower the 15-minute water immersion rate, the better the short-term water resistance.

[0032] [Equation 3]

[0033] 15-minute moisture impregnation rate (MIR-15M, weight %) = {(weight of aerogel mat after 15 minutes of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water} × 100

[0034] As described above, hydrophobic silica aerogel felt, which forms a hydrophobic silica aerogel within fibers, is a functional thermal insulation material that prevents moisture corrosion and is widely used in construction and industrial applications. Therefore, the silica aerogel felt needs to possess excellent thermal insulation and water resistance to prevent moisture penetration into the aerogel and maintain its insulation properties. To impart water resistance, a surface modification step is performed during the manufacture of the aerogel felt to make the aerogel surface hydrophobic, thereby inhibiting moisture penetration into the aerogel felt. This surface modification step introduces hydrophobic groups onto the outermost surface of the aerogel to ensure short-term water resistance. However, since the surface modification reaction begins at the outermost edge of the aerogel, it is difficult to introduce a sufficient amount of surface modifier into the aerogel. Under harsh conditions of prolonged and moderate exposure to moisture, the thermal insulation performance deteriorates as moisture eventually penetrates the aerogel, leading to moisture adsorption due to hydrogen bonds between hydroxyl groups present on the surface within the aerogel and water, which further degrades the durability of the aerogel.

[0035] Therefore, the present invention provides an aerogel mat with excellent long-term waterproofing by uniformly introducing hydrophobic groups on both the outermost and inner surfaces of the aerogel, thereby preventing water penetration into the aerogel. Specifically, the present invention provides an aerogel mat with excellent short-term, medium-term, and long-term waterproofing properties.

[0036] According to one embodiment of the present invention, the 28-day moisture impregnation rate (MIR-28D) of the aerogel felt, calculated by Equation 1 below, can be less than 100% by weight.

[0037] [Equation 1]

[0038] 28-day moisture impregnation rate (MIR-28D, weight %) = {(weight of aerogel mat after 28 days of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water} × 100

[0039] The moisture impregnation rate in Equation 1 above represents the increase in weight of the aerogel felt by immersing it in distilled water for an extended period. When the 28-day moisture impregnation rate is at or below 100% by weight, it can be seen that the durability of the aerogel can be prevented from deteriorating due to water adsorption caused by hydrogen bonds between hydroxyl groups present on the surface of the aerogel and water. As in this invention, to minimize the 28-day moisture impregnation rate, it is necessary to uniformly introduce hydrophobic groups on both the outermost and inner surfaces of the aerogel, which can be achieved by the manufacturing method of the aerogel felt according to the invention described below.

[0040] According to one embodiment of the present invention, the 28-day moisture immersion rate (MIR-28D) of the aerogel felt calculated by Equation 1 above can be 90% by weight or less, 70% by weight or less, or 50% by weight or less. When within the above range, the aerogel felt exhibits excellent long-term water resistance, thereby maximizing durability by resisting water penetration.

[0041] According to one embodiment of the present invention, the 96-hour moisture impregnation rate (MIR-96H) of the aerogel felt, calculated by Equation 2 below, can be less than 50% by weight.

[0042] [Equation 2]

[0043] 96-hour moisture impregnation rate (MIR-96H, weight %) = {(weight of aerogel mat after 96 hours of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water} × 100

[0044] The moisture impregnation rate in Equation 2 above represents the increase in weight of the aerogel felt by immersing it in distilled water for an average time. When the 96-hour moisture impregnation rate is at or below 50% by weight, as in the case of the 28-day moisture impregnation rate calculated by Equation 1 above, it has the effect of preventing the degradation of the aerogel's durability due to water adsorption caused by hydrogen bonds between water and hydroxyl groups present on the surface inside the aerogel. As in this invention, in order to minimize the 96-hour moisture impregnation rate, it is necessary to uniformly introduce hydrophobic groups on both the outermost surface and the inner surface of the aerogel, which can be implemented by the manufacturing method of the aerogel felt according to the invention described below.

[0045] According to one embodiment of the present invention, the 96-hour water immersion rate (MIR-96H) of the aerogel felt calculated by Equation 2 above can be less than 45% by weight or less than 40% by weight. When within the above range, the aerogel felt exhibits excellent medium-term and long-term water resistance, thereby maximizing durability by resisting water penetration.

[0046] According to one embodiment of the present invention, the 15-minute moisture impregnation rate (MIR-15M) of the aerogel felt, calculated by Equation 3 below, can be less than 20% by weight.

[0047] [Equation 3]

[0048] 15-minute moisture impregnation rate (MIR-15M, weight %) = {(weight of aerogel mat after 15 minutes of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water} × 100

[0049] The water impregnation rate in Equation 3 above represents the increase in weight of the aerogel felt by immersing it in distilled water for a short time. When the water impregnation rate is at most 20% by weight or less after 15 minutes, hydrophobic groups are sufficiently introduced onto the outermost surface of the aerogel, thereby preventing moisture from penetrating into the aerogel felt when exposed to moisture.

[0050] According to one embodiment of the present invention, the 15-minute water immersion rate (MIR-15M) of the aerogel felt calculated by Equation 3 above can be less than 15% by weight, less than 10% by weight, less than 5% by weight, less than 3% by weight, or less than 1.5% by weight. When within the above ranges, the aerogel felt exhibits excellent short-term water resistance, thereby maximizing the prevention of water penetration into the aerogel.

[0051] According to one embodiment of the invention, the aerogel mat may have a 28-day moisture impregnation rate (MIR-28D) calculated by Equation 1 above, satisfying Equation 4 below, and a 15-minute moisture impregnation rate (MIR-15M) calculated by Equation 3 above.

[0052] [Equation 4]

[0053] (MIR-28D)-(MIR-15M)≤100

[0054] Equation 4 above can be used to determine whether the aerogel felt can ensure sufficient water resistance based on the relationship between its long-term and short-term water resistance. Specifically, even if the 15-minute water immersion rate (MIR-15M), which represents the short-term water resistance of the aerogel felt, calculated using Equation 3 above, is low, it can be seen that hydrophobic groups are adequately introduced onto the outermost surface of the aerogel to prevent water penetration into the aerogel felt when exposed to moisture. However, if the aerogel felt is continuously exposed to moisture for a long period of time, it cannot be seen that all water penetration can be prevented. Therefore, if the 28-day water immersion rate (MIR-28D), which represents the long-term water resistance of the aerogel felt, calculated using Equation 1 above, increases rapidly relative to the 15-minute water immersion rate (MIR-15M), which represents the short-term water resistance of the aerogel felt, calculated using Equation 3 above, it cannot be seen that hydrophobic groups are uniformly introduced onto both the outermost and inner surfaces of the aerogel as in this invention. That is, according to one embodiment of the present invention, when the aerogel felt satisfies Equation 4 above, it has the effect of ensuring sufficient short-term water resistance, and at the same time, it prevents the degradation of the aerogel's durability caused by water adsorption due to hydrogen bonds between hydroxyl groups present on the surface inside the aerogel. In order to satisfy Equation 4 above, as in the present invention, hydrophobic groups need to be uniformly introduced on both the outermost surface and the inner surface of the aerogel, which can be implemented by the manufacturing method of the aerogel felt according to the present invention described below.

[0055] According to one embodiment of the invention, the aerogel felt may have a 28-day water immersion rate (MIR-28D) calculated by Equation 1 above and a 15-minute water immersion rate (MIR-15M) calculated by Equation 3 above, satisfying Equations 5, 6, 7, 8, or 9 below. In this case, since the 28-day water immersion rate (MIR-28D) representing long-term water resistance calculated by Equation 1 above is prevented from increasing rapidly relative to the 15-minute water immersion rate representing short-term water resistance calculated by Equation 3 above, the aerogel felt exhibits excellent short-term, medium-term, and long-term water resistance, thereby maximizing durability by resisting water penetration.

[0056] [Equation 5]

[0057] 1 ≤ (MIR-28D) - (MIR-15M) ≤ 90

[0058] [Equation 6]

[0059] 1 ≤ (MIR-28D) - (MIR-15M) ≤ 80

[0060] [Equation 7]

[0061] 1 ≤ (MIR-28D) - (MIR-15M) ≤ 70

[0062] [Equation 8]

[0063] 1 ≤ (MIR-28D) - (MIR-15M) ≤ 60

[0064] [Equation 9]

[0065] 1 ≤ (MIR-28D) - (MIR-15M) ≤ 50

[0066] According to one embodiment of the present invention, the amount of dust generated by the aerogel felt, calculated by the following Equation 10, can be less than 3.0% by weight.

[0067] [Equation 10]

[0068] Dust generation (by weight %) = {(Weight of aerogel mat before vibration - Weight of aerogel mat after vibration at 18Hz / 6mm) / Weight of aerogel mat before vibration} × 100

[0069] The dust generation amount in Equation 10 above represents the content of dust remaining in the aerogel felt as light and fine aerogel powder. The aerogel in the aerogel felt is manufactured as a unit, but in addition to the aerogel unit, dust as light and fine aerogel powder is inevitably generated during the manufacturing process. When the aerogel felt is constructed as an insulation material, this dust can cause reduced constructability, obstruct the operator's view, or pose a safety hazard to the operator due to the possibility of inhaling the dust. Therefore, according to one embodiment of the invention, when the dust generation amount is at most 3.0% by weight or less, it has the effect of preventing the reduction in constructability caused by residual dust in the aerogel felt and ensuring the safety of the operator.

[0070] According to one embodiment of the invention, the dust generation amount of the aerogel felt calculated by Equation 10 above can be less than 2.0% by weight, less than 1.5% by weight, less than 1.0% by weight, less than 0.5% by weight, or less than 0.4% by weight. When within the above ranges, the dust generation amount of the aerogel felt is minimized, thereby ensuring constructability and operator safety.

[0071] According to one embodiment of the invention, the room temperature (23±5°C) thermal conductivity of the aerogel felt can be below 30.0 mW / mK. Room temperature thermal conductivity is used to indicate the insulation properties of the aerogel felt. When its room temperature thermal conductivity is at or below 30.0 mW / mK, and when the aerogel felt is used as an insulation material, it has the effect of ensuring sufficient insulation.

[0072] According to one embodiment of the present invention, the room temperature (23±5℃) thermal conductivity of the aerogel felt can be below 25.0 mW / mK or below 20.0 mW / mK. When within the above range, it has the effect of maximizing the thermal insulation of the aerogel felt.

[0073] According to one embodiment of the invention, the aerogel felt includes an aerogel and a substrate for felting, wherein the aerogel can be formed inside and on the surface of the substrate for felting. As a specific example, the aerogel felt may have a large number of aerogel particles uniformly formed inside and on the surface of the substrate for felting.

[0074] Furthermore, according to one embodiment of the invention, the aerogel may contain hydrophobic groups on its inner surface. As a specific example, the aerogel may have hydrophobic groups uniformly introduced on both the outermost and inner surfaces of the aerogel, which can be implemented by the manufacturing method of the aerogel felt according to the invention described below.

[0075] According to one embodiment of the present invention, the aerogel felt can be effectively used as a thermal insulation material, insulating material or non-combustible material for aircraft, ships, automobiles, building structures, etc., as well as for insulation and cooling of factory facilities, such as pipes and industrial furnaces of various industrial facilities.

[0076] In addition, the present invention provides a method for manufacturing an aerogel felt to produce the aerogel felt.

[0077] To manufacture the aerogel felt according to the present invention, a manufacturing step is necessary to uniformly introduce hydrophobic groups onto both the outermost surface and the inner surface of the aerogel. Therefore, the present invention provides a method for manufacturing an aerogel felt that includes the aforementioned manufacturing steps and has a first aspect and a second aspect.

[0078] The first aspect of the manufacturing method of aerogel felt

[0079] A first aspect of the method for manufacturing an aerogel felt according to the present invention comprises: 1) preparing a silica sol; 2) impregnating the silica sol into a substrate for the felt; and 3) allowing the silica sol-substrate composite material for the felt to stand, wherein the silica sol comprises a silica precursor composition and a catalyst composition, and the catalyst composition comprises a hydrophobic agent, an alkaline catalyst, water, and an organic solvent, wherein the content of the alkaline catalyst may be from 0.4 parts by weight to 1.0 parts by weight based on 100 parts by weight of the silica sol.

[0080] In a first aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, the silica sol may be a precursor that can ultimately prepare silica aerogel through a gelation reaction, or it may be prepared by mixing a silica precursor composition and a catalyst composition.

[0081] In a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the silica precursor composition may comprise a silica precursor, an organic solvent, and water. In this case, the silica precursor contained in the silica precursor composition is a substance used to contain silica in the prepared aerogel. As an example, one or more selected from tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetrasec-butyl orthosilicate, tetratert-butyl orthosilicate, tetrahexyl orthosilicate, tetracyclohexyl orthosilicate, and tetra(dodecyl) orthosilicate, or their pre-hydrolyzed products, may be used. When using pre-hydrolyzed products, the addition of acid is unnecessary, the process of hydrolyzing the silica precursor can be shortened or omitted, and the effect of surface modification can be promoted. More specifically, in the present invention, pre-hydrolyzed polyethyl orthosilicate (HTEOS) may be used as the silica precursor.

[0082] Here, HTEOS is a pre-hydrolyzed polyethyl silicate oligomer material with a wide molecular weight distribution. Physical properties such as gelation time can be adjusted by modifying the degree of pre-hydrolysis (hydration) when synthesized from TEOS monomers into oligomer form. This allows for easy application based on the user's reaction conditions. Furthermore, it offers the advantage of producing reproducible physical properties in the final product.

[0083] In a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the amount of silica precursor used can be such that the silica content in the silica sol is from 0.1% by weight to 30% by weight, but the amount of silica precursor used is not limited thereto. When the silica content meets the above range, it is preferred to obtain aerogel felt with excellent mechanical and physical properties, especially its flexibility, and with improved thermal insulation effect.

[0084] In a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the organic solvent may specifically be an alcohol. In this case, the alcohol may be: a monohydric alcohol, such as methanol, ethanol, isopropanol, and butanol; or a polyhydric alcohol, such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, and sorbitol, and any one of them or a mixture of two or more of them may be used. Wherein, when considering miscibility with water and the aerogel, the alcohol may be a monohydric alcohol having 1 to 6 carbon atoms, such as methanol, ethanol, isopropanol, and butanol, and may be, for example, ethanol. Those skilled in the art can consider the degree of hydrophobicity in the ultimately prepared aerogel while simultaneously favoring surface modification reactions to use the aforementioned alcohols (organic solvents) and water in appropriate amounts.

[0085] In a first aspect of a method for manufacturing an aerogel felt according to an embodiment of the present invention, the catalyst composition is characterized by comprising a hydrophobic agent, an alkaline catalyst, water, and an organic solvent, wherein the content of the alkaline catalyst is from 0.4 parts by weight to 1.0 parts by weight based on 100 parts by weight of silica sol.

[0086] In a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the catalyst composition comprises water along with a hydrophobic agent. Therefore, the hydrophobic agent contained in the catalyst composition can be activated, and when the hydrophobic agent is activated, aging and surface modification can be performed without the separate use of aging solutions and surface modification solutions. Here, activation of the hydrophobic agent refers to a hydrolysis reaction of functional groups other than alkyl groups, such as alkoxy groups, halogen groups, etc., of the hydrophobic agent, thereby forming hydroxyl groups (-OH) at the positions of the functional groups. When the hydrophobic agent is activated, its reactivity with the -Si-O- functional groups forming the network structure in the silica wet gel can be greatly increased, allowing the hydrophobic agent and the silica wet gel to react with each other without separate additional catalysts and solvents to achieve structural reinforcement or surface modification. Furthermore, this has the effect of improving the long-term waterproofness of the aerogel felt.

[0087] In a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, when the catalyst composition contains a hydrophobic agent but not water, the hydrophobic agent cannot be activated. Therefore, in order to subsequently achieve aging and surface modification, as in conventional methods, aging and surface modification processes requiring large amounts of solvent must be carried out at high temperatures, and the problem remains that aging and surface modification reactions do not occur even when left to stand at room temperature. Therefore, structural reinforcement cannot be achieved, resulting in shrinkage of the gel structure during drying, and due to the lack of surface modification reactions, the problem arises that hydrophobic silica aerogel felts cannot be manufactured.

[0088] In a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, an alkylsilane compound can be used as the hydrophobic agent. In this case, the hydrophobic agent can participate in the gelation reaction as a co-precursor and can hydrophobize the formed silica wet gel felt. Since the alkylsilane compound can gel with the silica precursor in the gelation step, or the alkylsilane compound trapped in the gel can be aged or surface modified in the settling step and form an alkyl-Si-O-Si network to hydrophobize the silica wet gel felt, the surface modification step can be omitted when manufacturing the hydrophobic silica aerogel felt. Therefore, the amount of organic solvent and surface modifier used in the surface modification step can be reduced, and the process time and manufacturing cost can be shortened. In addition, the amount of ammonia generated when the surface of the silica wet gel is surface modified can be greatly reduced, which makes it possible to improve the reuse efficiency of the waste liquid generated after the manufacture of the silica aerogel felt, and when the waste liquid is reused, the hydrophobic agent component contained in the waste liquid can be contained again in the silica sol, thereby greatly reducing the amount of hydrophobic agent used through reuse.

[0089] Here, the hydrophobic agent can specifically be an alkylsilane compound as described above, and there is no limitation on its type, as long as it is an alkylsilane compound containing an alkyl group that causes hydrophobicity and a silane functional group capable of reacting with the -Si-O- functional group of the wet gel. More specifically, the hydrophobic agent may include one or more selected from trimethylethoxysilane (TMES), trimethylsilanol (TMS), trimethylchlorosilane (TMCS), methyltrimethoxysilane (MTMS), methyltrimethoxysilane (MTES), dimethyldiethoxysilane (DMDEOS), ethyltriethoxysilane, and phenyltriethoxysilane.

[0090] Furthermore, in a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, more preferably, the hydrophobic agent does not contain silazane compounds such as hexamethyldisilazane. When silazane compounds are included, they begin to decompose and produce ammonia upon contact with an organic solvent. Therefore, once a silazane compound is introduced into a catalyst composition containing an organic solvent, a gelation reaction immediately begins due to the high pH formed by the production of ammonia. Therefore, it is preferable not to include silazane compounds in order to prevent undesirable gelation reactions and to easily control the gelation time by changing the amount of catalyst.

[0091] Furthermore, in a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, based on 100 parts by weight of silica sol, the content of the hydrophobic agent can be from 3 parts by weight to 15 parts by weight, specifically from 5 parts by weight to 10 parts by weight, and more specifically from 6 parts by weight to 8 parts by weight. When within the above range, the hydrophobicity efficiency (surface modification efficiency) compared to the amount used can be further improved.

[0092] Furthermore, in a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the catalyst composition may contain 3 to 8 equivalents of water based on 1 equivalent of a hydrophobic agent. Specifically, the water content may be 4 to 8 equivalents, more preferably 5 to 6 equivalents, based on 1 equivalent of a hydrophobic agent. When the water content is 3 equivalents or more based on 1 equivalent of a hydrophobic agent, the hydrophobic agent can be sufficiently activated, making it easy to achieve structural reinforcement and surface modification of the wet gel without additional catalysts, surface modifiers, and solvents. Therefore, it is preferred that silica aerogel felts with excellent hydrophobicity can be manufactured even without wet aging and separate surface modification processes requiring high temperature conditions and large amounts of organic solvents and surface modifiers. In addition, when the water content is 8 equivalents or less based on 1 equivalent of a hydrophobic agent, the amount of water in the wet gel felt can be controlled. Therefore, water is effectively removed during supercritical drying to suppress shrinkage of the aerogel due to water, thereby further improving thermal conductivity and hydrophobicity.

[0093] Furthermore, in a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, based on 100 parts by weight of all silica sol, the content of the alkali catalyst can be from 0.4 parts by weight to 1.0 parts by weight, specifically from 0.6 parts by weight to 1.0 parts by weight, and more specifically from 0.6 parts by weight to 0.8 parts by weight. When the content of the alkali catalyst is less than 0.4 parts by weight, the reactivity between the hydrophobic agent and the surface of the silica gel is weak during the settling process in step 3), which causes the problem that surface modification cannot be achieved. When the content is greater than 1.0 parts by weight, the problem is that the gelation rate is too high, making it difficult to prepare a uniform gel. In addition, due to the formation of an uneven gel, the physical properties deteriorate.

[0094] In a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, an alkaline catalyst can be used without limitation, as long as it is a substance capable of forming the pH conditions necessary for gelation. For example, the alkaline catalyst can be an inorganic base such as sodium hydroxide and potassium hydroxide, or an organic base such as ammonium hydroxide.

[0095] Specifically, the organic base may be ammonium hydroxide (NH4OH), tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), methylamine, ethylamine, isopropylamine, monoisopropylamine, diethylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, choline, monoethanolamine, diethanolamine, 2-aminoethanol, 2-(ethylamino)ethanol, 2-(methylamino)ethanol, N-methyldiethanolamine, dimethylaminoethanol, diethylaminoethanol, methamintriethanol, 2-(2-aminoethoxy)ethanol, 1-amino-2-propanol, triethanolamine, monopropanolamine, or dibutanol, and mixtures of two or more of them may be used. More specifically, the base catalyst may be ammonium hydroxide (ammonia water; NH4OH).

[0096] In addition, in a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the organic solvent is the same as described above, and the amount of organic solvent can be appropriately adjusted taking into account the compatibility with water and wet gel, as well as the ease of structural reinforcement and surface modification.

[0097] Furthermore, in a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the catalyst composition may be included in an amount such that the pH of the silica sol is 4 to 8. When included in an amount such that the pH of the silica sol meets the above-mentioned range, gelation can be easily and effectively achieved. Moreover, the catalyst composition is added in the liquid phase as an alkaline catalyst diluted in water and an organic solvent, thereby preventing the problem of catalyst precipitation.

[0098] According to an embodiment of the present invention, a method for manufacturing an aerogel felt according to a first aspect of a method for manufacturing an aerogel felt includes: 1) preparing a silica sol; 2) impregnating the silica sol into a substrate for the felt; and 3) allowing the silica sol-substrate composite material for the felt to stand, wherein the silica sol is the silica sol described above.

[0099] In a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, step 1) is the step of preparing a silica sol, which can be carried out by mixing a silica precursor composition and a catalyst composition. In this case, the silica sol, the silica precursor composition, and the catalyst composition are all the same as described above. Furthermore, the mixing of the silica precursor composition and the catalyst composition can be carried out under conditions of room temperature and atmospheric pressure.

[0100] In a first aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, since the above-mentioned silica sol is prepared in step 1), structural reinforcement and surface modification can be achieved even when the silica sol is left to stand in step 3) without additional alkaline catalyst, surface modifier and organic solvent - composite material for the substrate of the felt.

[0101] In a first aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, step 2) is the step of forming a silica sol-composite material for a substrate of felt, and can be carried out by impregnating the silica sol of step 1) into the substrate for felt.

[0102] In a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the substrate for the felt may specifically be a porous substrate in order to improve the thermal insulation properties of the silica aerogel felt. When a porous substrate for the felt is used, silica sol can easily penetrate into the substrate, thereby uniformly forming an aerogel inside the substrate for the felt, so that the manufactured silica aerogel felt can have excellent thermal insulation properties.

[0103] In a first aspect of a method for manufacturing an aerogel felt according to an embodiment of the present invention, the felt substrate may be a film, sheet, web, fiber, porous body, foam, nonwoven fabric, or a laminate of two or more layers thereof. Furthermore, depending on the intended use of the felt substrate, surface roughness or patterning may be formed on its surface. Specifically, the felt substrate may be a fiber capable of further improving thermal insulation performance by including spaces or pores, and may have low thermal conductivity, the spaces or pores allowing aerogel to easily form within the felt substrate.

[0104] In a first aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, the felt substrate may be polyamide, polybenzimidazole, polyaramid, acrylic resin, phenolic resin, polyester, polyetheretherketone (PEEK), polyolefin (polyethylene, polypropylene, copolymers thereof, etc.), cellulose, carbon, cotton, wool, hemp, nonwoven fabric, glass fiber, ceramic wool, etc.

[0105] In a first aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, step 3) is a step of allowing silica sol-composite material for the substrate of the felt to stand, and gelation, aging and surface modification can be performed in step 3).

[0106] Furthermore, in a first aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, since the silica sol of step 1) described above is used, aging and surface modification can be easily achieved after gelation without the use of separate surface modification solutions and aging solutions (alkali catalyst and solvent). Because wet aging and surface modification processes using separate surface modification solutions are not performed as described above, the amount of solvent and surface modifier used can be significantly reduced compared to conventional silica aerogel felt manufacturing processes. Moreover, since the amount of alkali catalyst components included in wet aging and the amount of ammonia generated by the surface modification reaction can be significantly reduced, the amount of ammonia in the waste liquid generated after manufacturing the aerogel felt is reduced, thereby improving the waste liquid reuse efficiency. Furthermore, this has the effect of improving the long-term waterproofness of the aerogel felt.

[0107] In a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, step 3) can be carried out at room temperature, and aging and surface modification can be more easily achieved at the aforementioned temperature. Furthermore, room temperature can specifically refer to a temperature of 15°C to 30°C or 15°C to 25°C. Furthermore, step 3) can be carried out for 5 hours to 48 hours, preferably 10 hours to 38 hours, more preferably 15 hours to 24 hours.

[0108] Furthermore, in a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the gelation time can be easily adjusted by adjusting the amount of catalyst in the catalyst composition to produce a silica aerogel with the desired physical properties. In this case, the gelation time can preferably be adjusted to 1 minute to 25 minutes, specifically 5 minutes to 10 minutes.

[0109] In a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the gel can be formed into a network structure from a silica precursor material, wherein the network structure can be a planar mesh structure with one or more types of atomic arrangements where specific polygons are connected to each other, or a structure in which specific polyhedra share their vertices, edges, faces, etc. to form a three-dimensional skeleton structure.

[0110] In addition, in a first aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, a drying step may be included after step 3), wherein the silica wet aerogel felt is dried to prepare hydrophobic silica aerogel.

[0111] Meanwhile, in a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, a washing step may be performed before drying. Washing is a step to remove impurities (sodium ions, unreacted substances, byproducts, etc.) and residual ammonia generated during the reaction process in order to obtain a high-purity hydrophobic silica aerogel. The residual ammonia can be reacted with CO2 in the supercritical drying process to generate ammonium carbonate, and washing can be carried out by dilution or displacement using a nonpolar organic solvent.

[0112] In a first aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the drying step can be performed by a process that removes the solvent while maintaining the pore structure of the aged silica gel, and the drying step can be performed by supercritical drying. The supercritical drying process can be carried out using supercritical carbon dioxide. Carbon dioxide (CO2) is gaseous at room temperature and atmospheric pressure. However, when the temperature and pressure exceed predetermined temperature and pressure limits known as the supercritical point, no evaporation process occurs, causing carbon dioxide to become a critical state in which it is indistinguishable from a gas. Carbon dioxide in the critical state is called supercritical carbon dioxide. Supercritical carbon dioxide has a molecular density close to that of a liquid, yet it has a low viscosity, thus exhibiting properties close to those of a gas. Therefore, supercritical carbon dioxide has a high diffusion rate and high thermal conductivity, resulting in high drying efficiency and a shorter drying process time.

[0113] In a first aspect of a method for manufacturing an aerogel felt according to an embodiment of the present invention, a supercritical drying process is performed involving solvent replacement, wherein aged silica gel is placed in a supercritical drying reactor, which is filled with liquid CO2, and the alcohol solvent inside the silica aerogel is replaced by CO2. Then, the temperature is increased to 40°C to 80°C at a predetermined heating rate, specifically 0.1°C / min to 1°C / min, and the pressure is maintained above the pressure at which carbon dioxide becomes supercritical, specifically 100 bar to 170 bar, to maintain the carbon dioxide in the supercritical state for a predetermined amount of time, specifically 20 minutes to 1 hour. Typically, carbon dioxide becomes supercritical at a temperature of 31°C and a pressure of 73.8 bar. The carbon dioxide is maintained at the predetermined temperature and pressure to remain in the supercritical state for 2 hours to 12 hours, more specifically 2 hours to 6 hours. After this, the pressure is typically reduced to end the supercritical drying process, thereby manufacturing the aerogel felt.

[0114] In a first aspect of a method for manufacturing an aerogel felt according to an embodiment of the present invention, as a result of the above-described drying process, a felt comprising porous silica aerogel having nanoscale pores and / or a felt comprising porous silica aerogel can be manufactured. The silica aerogel possesses excellent physical properties, particularly low tap density and high porosity, as well as high hydrophobicity, and the felt containing it, comprising silica aerogel, exhibits excellent mechanical flexibility and low thermal conductivity.

[0115] In addition, in a first aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, a compression process for controlling the thickness and making the internal structure and surface shape of the felt uniform, a molding process for having a suitable shape or form according to the application, or a lamination process for laminating individual functional layers may be performed before or after the drying process.

[0116] The second aspect of the manufacturing method of aerogel felt

[0117] A second aspect of the method for manufacturing an aerogel felt according to the present invention comprises: 1) introducing a catalytic sol and a substrate for felt into a reaction vessel to impregnate the catalytic sol into the substrate for felt; and 2) rotating the substrate for felt impregnated with the catalytic sol to perform gelation, wherein the catalytic sol comprises a silica precursor composition, and the silica precursor composition comprises a silicate containing hydrophobic groups and a tetraalkyl silicate, wherein the molar ratio of the silicate containing hydrophobic groups to the tetraalkyl silicate is from 60:40 to 98:2.

[0118] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, step 1) is the step of impregnating a catalytic sol into a substrate for the felt to prepare an aerogel felt, wherein the catalytic sol can be prepared, and then the prepared catalytic sol and the substrate for the felt can be introduced into a reaction vessel to impregnate the catalytic sol into the substrate for the felt.

[0119] Furthermore, in a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, in step 1), the order in which the substrate for the felt and the catalytic sol are introduced into the reaction vessel is not particularly limited, as long as the substrate for the felt and the catalytic sol are introduced. Specifically, in step 1), the introduction can be performed by any of the following methods: introducing the substrate for the felt into the reaction vessel and then introducing the catalytic sol; introducing the catalytic sol into the reaction vessel and then introducing the substrate for the felt; and introducing the substrate for the felt while simultaneously introducing the catalytic sol into the reaction vessel. The method of introducing the substrate for the felt and then introducing the catalytic sol is more desirable for obtaining a more uniform impregnation. Specifically, when the substrate for the felt is introduced first, it can be rotated during the introduction of the catalytic sol to induce a more uniform impregnation.

[0120] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, in step 1), as described above, impregnation can be performed while the substrate for the felt is being rotated. When impregnation is performed while the substrate for the felt is being rotated, the catalyzed sol can uniformly contact all surfaces of the substrate for the felt to induce uniform impregnation, which is more desirable.

[0121] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the catalytic sol can be prepared by mixing the sol with an alkaline catalyst, wherein the alkaline catalyst is used to promote gelation in step 2) by increasing the pH of the sol. Here, there are no limitations on the sol, as long as it is a substance capable of forming a porous gel through a sol-gel reaction, and specifically, it can include inorganic sols, organic sols, or combinations thereof. The inorganic sols can include: zirconium oxide, yttrium oxide, hafnium oxide, aluminum oxide, titanium dioxide, cerium dioxide, silicon dioxide, magnesium oxide, calcium oxide, magnesium fluoride, calcium fluoride, and combinations thereof; the organic sols can be: polyacrylates, polyolefins, polystyrene, polyacrylonitrile, polyurethane, polyimide, polyfurfuryl alcohol, phenol-furfuryl alcohol, melamine-formaldehyde, resorcinol-formaldehyde, cresol-formaldehyde, phenol-formaldehyde, polyvinyl alcohol dialdehyde, polycyanurate, polyacrylamide, various epoxy resins, agar, agarose, and combinations thereof. Furthermore, the sol may preferably be a silica sol in order to ensure excellent miscibility with the substrate used for the felt, further improve the porosity when formed into a gel, and manufacture aerogel felt with low thermal conductivity.

[0122] In a second aspect of a method for manufacturing an aerogel felt according to an embodiment of the present invention, the sol comprises a sol precursor, water, and an organic solvent, and can be prepared by mixing the sol precursor, water, and organic solvent. When the catalytic sol according to an embodiment of the present invention is a catalytic silica sol, in step 1), the catalytic silica sol can be prepared by mixing a silica sol with an alkaline catalyst, wherein the silica sol can be prepared by mixing a silica precursor composition, water, and an organic solvent. Furthermore, the silica sol can be hydrolyzed at a low pH to promote gelation, in which case an acid catalyst can be used to lower the pH. The silica precursor composition that can be used to prepare the silica sol may include silicon-containing alkoxide compounds, specifically, may include silicates and tetraalkyl silicates containing hydrophobic groups.

[0123] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, when preparing the aerogel, the silicate containing hydrophobic groups is used to impart hydrophobicity to the aerogel without a surface modification step, and may be one or more selected from methyltriethoxysilane (MTES), trimethylethoxysilane (TMES), trimethylsilanol (TMS), methyltrimethoxysilane (MTMS), dimethyldiethoxysilane (DMDEOS), ethyltriethoxysilane (ETES), and phenyltriethoxysilane (PTES). When the silicate containing hydrophobic groups is included in the silica precursor composition as described above, the surface modification step can be omitted, and therefore, a regeneration process is not required when recovering the solvent. Furthermore, since hydrophobic groups can be uniformly introduced from the interior to the exterior of the aerogel, the hydrophobicity is maximized, thereby allowing water with high surface tension to be easily expelled, enabling atmospheric pressure drying in the subsequent drying step. Furthermore, this has the effect of improving the long-term water resistance of the aerogel felt.

[0124] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the tetraalkyl silicate is used to enhance the strength of the aerogel and ensure thermal insulation properties, and can be a tetraalkyl silicate such as tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetrasec-butyl orthosilicate, tetratert-butyl orthosilicate, tetrahexyl orthosilicate, tetracyclohexyl orthosilicate, and tetra(dodecyl) orthosilicate. Specifically, the silica precursor according to an embodiment of the present invention can be tetraethyl orthosilicate (TEOS).

[0125] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the molar ratio of the silicate containing hydrophobic groups to the tetraalkyl silicate in the silica precursor composition can be from 60:40 to 98:2. When within the above range, the strength and thermal insulation properties of the aerogel can be maximized during supercritical drying. Furthermore, when drying at atmospheric pressure, the molar ratio of the silicate containing hydrophobic groups to the tetraalkyl silicate in the silica precursor composition can be from 85:15 to 98:2, or from 90:10 to 98:2. When within the above range, the strength and thermal insulation properties of the aerogel can be efficiently ensured, and furthermore, a decrease in thermal insulation properties can be prevented by preventing shrinkage during atmospheric pressure drying. The silica precursor composition can be used in an amount such that the content of silica (SiO2) contained in the silica sol is from 3% to 30% by weight, 5% to 20% by weight, or 6% to 12% by weight. When within the aforementioned range, a sufficient amount of silica aerogel can be ensured in the final manufactured felt, allowing for the expectation of an ideal level of thermal insulation. Furthermore, preventing excessive silica aerogel formation prevents degradation of the felt's mechanical properties, particularly its flexibility.

[0126] Furthermore, in a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, any substance can be used as the organic solvent for preparing the sol without limitation, as long as it is compatible with the sol precursor and water. Specifically, polar organic solvents can be used, and more specifically, alcohols can be used. Here, the alcohol can specifically be: monohydric alcohols, such as methanol, ethanol, isopropanol, and butanol; or polyhydric alcohols, such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, and sorbitol, and any one of them or a mixture of two or more of them can be used. Wherein, when considering its miscibility with water and the aerogel to be prepared, the alcohol can be a monohydric alcohol having 1 to 6 carbon atoms, such as methanol, ethanol, isopropanol, and butanol. The above-mentioned organic solvents can be used in appropriate amounts considering the content of the final prepared aerogel.

[0127] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the silica sol may comprise a silica precursor composition and water in a molar ratio of 1:10 to 1:1. Furthermore, the silica precursor composition and organic solvent may be contained in a weight ratio of 1:2 to 1:9, and preferably, in a weight ratio of 1:2 to 1:6. When the silica precursor composition, water, and organic solvent meet the above-mentioned molar or weight ratios, the yield of the aerogel can be further increased, thereby improving the thermal insulation properties.

[0128] Furthermore, in a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, any acid catalyst that can be further included in the sol can be used without limitation, and can produce a pH of 3 or lower. As an example, hydrochloric acid, nitric acid, or sulfuric acid can be used. In this case, the acid catalyst can be added in an amount that produces a pH of 3 or lower in the sol, and can be added in the form of an aqueous solution dissolved in an aqueous solvent.

[0129] In addition, in a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, the alkaline catalyst in the sol that can be used for catalysis can be an inorganic base such as sodium hydroxide and potassium hydroxide, or an organic base such as ammonium hydroxide. Specifically, the alkaline catalyst may be selected from one or more of sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), ammonia (NH3), ammonium hydroxide (NH4OH; ammonia water), tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), methylamine, ethylamine, isopropylamine, monoisopropylamine, diethylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, choline, monoethanolamine, diethanolamine, 2-aminoethanol, 2-(ethylamino)ethanol, 2-(methylamino)ethanol, N-methyldiethanolamine, dimethylaminoethanol, diethylaminoethanol, subaminotriethanol, 2-(2-aminoethoxy)ethanol, 1-amino-2-propanol, triethanolamine, monopropanolamine, dibutanolamine, and pyridine, preferably sodium hydroxide, ammonia, ammonium hydroxide, or mixtures thereof. The alkaline catalyst can be included in an amount that makes the pH of the sol between 7 and 11. If the pH of the sol is outside this range, gelation in step 2) cannot be easily achieved, or the gelation rate will be too low, resulting in decreased processing performance. Furthermore, since the alkali precipitates when introduced as a solid phase, it is preferable to add the alkali in the form of a solution diluted with an aqueous solvent or the aforementioned organic solvent. In this case, the dilution ratio of the alkaline catalyst to the organic solvent, specifically an alcohol, can be from 1:4 to 1:100, based on volume.

[0130] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, additives may be added to the catalytic sol as needed. In this case, all known additives that can be added during the manufacture of aerogels can be used as the additives, for example, additives such as light-blocking agents, flame retardants, etc. The substrate for the felt can be introduced in a suitable form that facilitates introduction, depending on the shape of the reaction vessel. Specifically, the substrate for the felt can be introduced into the reaction vessel in the form of a roll wound on a spool to facilitate rotation in step 2) described later. In this case, the spool can be an axis capable of rotating the substrate for the felt, and any material can be used without limitation, as long as it can be wound around the substrate for the felt. As an example, a polygonal cylinder can be used, preferably a cylinder with dimensions suitable for the interior of the reaction vessel.

[0131] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the reel may include: a winding rod capable of winding the substrate for the felt in a coil; and a support plate supporting the sides of the substrate for the felt such that the substrate for the felt wound on the winding rod does not shift during rotation. Preferably, the winding rod has a plurality of holes, allowing the catalytic sol to be easily impregnated into the interior of the substrate for the felt. Meanwhile, to allow the catalytic sol to be introduced into the sides of the substrate for the felt, a mesh-type support plate may be used, or the support plate may include a plurality of holes. Any material having sufficient strength to support the felt can be used as the material of the reel. Specifically, stainless steel, PE, PP, and Teflon may be used.

[0132] In a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, after the substrate for felt is wound onto the spool, the spool can be placed into a reaction vessel and fixed. Here, the spool can be fixed at any position within the reaction vessel. However, in order to improve production efficiency by introducing a large quantity of substrate for felt into a reaction vessel of a predetermined volume, the spool can preferably be fixed at the central portion of the reaction vessel. Furthermore, the spool can be arranged such that the long axis of the spool is parallel to the long axis of the reaction vessel.

[0133] Furthermore, in a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, in order to improve the thermal insulation performance of the aerogel felt, the substrate for the felt can specifically be a porous substrate. When a porous substrate for the felt is used, the catalyzed sol can easily penetrate into the substrate, thereby uniformly forming an aerogel inside the substrate for the felt, so that the manufactured aerogel felt can have excellent thermal insulation performance.

[0134] According to one embodiment of the invention, the substrate for the aerogel felt, which can be used according to a second aspect of the method for manufacturing the aerogel felt, can be a film, sheet, web, fiber, foam, nonwoven fabric, or a laminate of two or more layers thereof. Furthermore, depending on the intended use of the substrate for the felt, surface roughness or patterning can be formed on its surface. More specifically, the substrate for the felt can be a fiber capable of further improving thermal insulation performance by including spaces or voids through which aerogel can be easily inserted. Additionally, the substrate for the felt may preferably have a low thermal conductivity.

[0135] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the substrate for the felt may be polyamide, polybenzimidazole, polyaramid, acrylic resin, phenolic resin, polyester, polyetheretherketone (PEEK), polyolefin (e.g., polyethylene, polypropylene, copolymers thereof, etc.), cellulose, carbon, cotton, wool, hemp, nonwoven fabric, glass fiber, ceramic wool, etc. More specifically, the substrate for the felt in the present invention may be glass fiber.

[0136] In a second aspect of the method for manufacturing aerogel felt according to an embodiment of the invention, the reaction vessel may be a reaction vessel for gelation, and any shape, such as polygonal or cylindrical, may be used, as long as it provides space in which the substrate for felt, impregnated with the catalytic sol, can be rotated. However, a cylindrical reaction vessel may be preferred for the advantages of introducing the substrate for felt wound in roll form and for the advantages of rotating the substrate for felt impregnated with the catalytic sol during the gelation reaction.

[0137] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, in step 1), when the catalytic sol is introduced, the substrate for the felt can be gently pressed downwards to achieve sufficient impregnation in order to improve the bonding between the substrate for the felt and the catalytic sol. Subsequently, the substrate for the felt can be pressed to a predetermined thickness at a constant pressure to remove excess sol, thereby shortening the drying time. In another embodiment, when the catalytic sol is introduced into the reaction vessel and the substrate for the felt is sufficiently impregnated such that the liquid level in the reaction vessel no longer changes, a drain valve connected to the reaction vessel can be opened to recover any remaining sol.

[0138] In addition, in a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the catalytic sol and the substrate for the felt can each be introduced in a certain amount, specifically in an amount of 1% to 100% of the internal volume of the reaction vessel, and in terms of shortening the gelation time in step 3) and uniformly forming aerogel inside the substrate for the felt, they can be introduced in an amount of 1% to 60% of the volume of the reaction vessel, more specifically in an amount of 10% to 60%, and even more preferably in an amount of 30% to 60%.

[0139] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the amount of catalytic sol introduced can be 80% to 120%, preferably 90% to 110%, based on the volume of the substrate for the felt. Furthermore, preferably, the amounts of the substrate for the felt and the catalytic sol introduced can satisfy the aforementioned introduction ratio between them, provided that the amount introduced relative to the reaction vessel is satisfied. When the catalytic sol satisfies the aforementioned introduction ratio (introduction amount) relative to the volume of the substrate for the felt, the catalytic sol is more uniformly impregnated on the substrate for the felt, resulting in aerogel felt to be manufactured having more uniform physical properties. Furthermore, since the catalytic sol can be completely impregnated on the substrate for the felt, raw material loss and the problem of individual gelation of the catalytic sol can be prevented.

[0140] In a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, step 2) is used to manufacture a wet gel felt composite material (wet gel felt), and can be carried out by rotating a substrate for felt impregnated therein with a catalytic sol to perform gelation.

[0141] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the rotation of the substrate for the felt impregnated with the catalytic sol can be performed by any method or apparatus, as long as the method or apparatus allows the rotation during the gelation process to take place in the reaction vessel. Specifically, when the substrate for the felt is introduced and fixed while being wound onto the spool in step 1) above, the substrate for the felt impregnated with the catalytic sol is present in the reaction vessel while being wound onto the spool, and therefore, the substrate for the felt impregnated with the catalytic sol can be rotated by rotating the spool.

[0142] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the gel can be formed into a network structure by a catalytic sol, wherein the network structure can represent a planar mesh structure with one or more types of atomic arrangements where specific polygons are connected to each other, or a structure in which specific polyhedra share their vertices, edges, faces, etc. to form a three-dimensional skeleton structure.

[0143] In a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, the gelation reaction can be carried out after sealing the reaction vessel containing the catalyzed sol and the substrate for the felt. Furthermore, according to an embodiment of the present invention, rotation can be performed by setting the long axis in the transverse direction, i.e., the horizontal direction. If the reaction vessel (body) is a cylindrical reaction vessel, the cylindrical reaction vessel can be laid down and rotated. That is, the axis of rotation of the reaction vessel of the present invention can be horizontal, but is not limited thereto.

[0144] In a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, there is no limitation on the type of apparatus used for manufacturing the aerogel felt, as long as it includes a reaction vessel (body) and is capable of rotating a substrate for the felt containing a catalytic sol impregnated in the reaction vessel. Any apparatus known in the art can be used, as long as it is capable of rotation. Specifically, any known apparatus can be used, as long as it is capable of fixing the position of a spool in the reaction vessel and rotating the spool whose position is fixed. Examples of apparatuses for manufacturing aerogel felt that can be used in the present invention will be described later.

[0145] In addition, in a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, after step 1) above is completed, step 2) above can be started to perform step 1) and step 2) above in sequence.

[0146] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, step 2) may be started before step 1) ends. As described above, when step 2) is performed before step 1) ends, all the catalytic sol can be introduced into the reaction vessel until gelation is complete, specifically before gelation is complete.

[0147] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the rotational speed in step 2) above can be applied without limitation, as long as it is a rotational speed that allows the aerogel to form uniformly in the felt. As an example, gelation can be performed while rotating at a speed of 1 rpm to 300 rpm, preferably 5 rpm to 150 rpm, 5 rpm to 100 rpm, and more preferably 10 rpm to 30 rpm. When the reaction vessel meets the rotational speed within the above range, the sol can be uniformly impregnated onto the substrate used for the felt, resulting in more uniform aerogel formation during the gelation process. Therefore, a very uniform thermal conductivity throughout the aerogel felt can be ensured, and the process of manufacturing the aerogel felt has the advantage of improved safety by increasing the stability of the reaction vessel and the apparatus used to rotate the reaction vessel.

[0148] In a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, the catalytic sol and the substrate for felt are placed entirely into a reaction vessel for gelation, thereby manufacturing aerogel felt. This eliminates the need for a separate moving element such as a conveyor belt, unlike the commonly used roll-to-roll method, thus offering the advantage of significantly saving space during the manufacturing process. Furthermore, in the roll-to-roll method, when the substrate for felt is placed on a moving element, the catalytic sol is applied to the substrate for felt, and then the moving element is continuously moved for gelation, gelation does not occur simultaneously across the entire substrate for felt, but rather sequentially over time while the substrate for felt and the catalytic sol are continuously supplied. Therefore, the problem is that even when using substrates for felt with the same thickness and length, gelation takes significantly longer than the gelation process according to an embodiment of the present invention. Specifically, the longer the substrate for felt, the more significant the problem of increased gelation time becomes in order to achieve sufficient gelation across the entire substrate for felt. However, according to an embodiment of the present invention, the simultaneous gelation of the sol across the entire substrate for felt allows for a significant reduction in manufacturing time. Furthermore, the length and thickness of the substrate used for felt do not affect the gelation time, which means that even when using a long substrate for felt, the manufacturing time can be significantly shortened to maximize process efficiency.

[0149] Furthermore, in a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, centrifugal and centripetal forces are applied because gelation occurs simultaneously with the rotation of the reaction vessel. Therefore, compared to roll-to-roll methods where the reaction vessel is not rotated or gelation occurs on a moving element, an aerogel felt in which the aerogel is more uniformly dispersed can be manufactured, resulting in an aerogel felt with a thickness that is the same as or very similar to the thickness of the substrate used for the felt, and exhibiting excellent thermal insulation properties.

[0150] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the aging step can be carried out by allowing the wet aerogel felt composite material to stand at an appropriate temperature as a process to fully realize the chemical changes. The aging step can more firmly form the shaped network structure, thereby improving the mechanical stability of the aerogel felt of the present invention.

[0151] In a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, the aging step of the present invention can be carried out in the presence of a wet aerogel felt composite material by allowing the wet aerogel felt composite material to stand at an appropriate temperature, or, as another example, by adding an alkaline catalyst, such as sodium hydroxide (NaOH), potassium hydroxide (KOH), ammonium hydroxide (NH4OH), triethylamine, pyridine, etc., diluted to a concentration of 1% to 10% in an organic solvent. In this case, the Si-O-Si bonding in the aerogel is maximally induced, making the network structure of the silica gel more robust, thereby having the effect of maintaining the pore structure during the subsequent rapid drying process. Here, the organic solvent can be the alcohol (polar organic solvent) described above, and specifically, can include ethanol.

[0152] Furthermore, in a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, the aging step should be carried out within an appropriate temperature range to achieve optimized pore structure enhancement. The aging step of the present invention can be carried out by allowing the wet aerogel felt composite material to stand at a temperature of 30°C to 70°C for 1 to 20 hours, regardless of the introduction of an alkaline catalyst. When the aging temperature is below 30°C, the aging time becomes too long, which increases the total process time and leads to a decrease in productivity. When the aging temperature is above 70°C, this temperature exceeds the boiling point of ethanol, resulting in increased solvent loss due to evaporation, which increases raw material costs.

[0153] Furthermore, in a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, the aging step can be carried out in a separate reaction vessel after the gelled silica wet aerogel felt has been recovered, or it can be carried out inside a reaction vessel that has already undergone gelling. In terms of process efficiency and equipment simplification, the aging step can preferably be carried out in a reaction vessel that has already undergone gelling. Moreover, when the aging step is carried out in a reaction vessel that has already undergone gelling, the wet aerogel felt composite material prepared in step 3) can be rotated, and when aging is performed while the composite material is rotated, the aging solvent can penetrate better and, after penetration, can be better dispersed in the wet aerogel felt composite material. Therefore, it has the advantage of significantly improving aging efficiency.

[0154] Furthermore, in a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, a solvent replacement step may be performed prior to the drying step of manufacturing the aerogel felt from the wet gel felt composite material. The wet gel of the wet gel felt composite material has pores filled with a solvent containing water and / or an organic solvent. When the drying step of the wet gel felt composite material is performed to remove the solvent, the liquid solvent evaporates into a gas phase, and shrinkage and rupture occur in the pore structure due to the surface tension of the solvent at the gas / liquid interface. Therefore, the specific surface area in the finally prepared silica aerogel is reduced, and the pore structure is altered. Therefore, in order to maintain the pore structure of the wet gel, the surface tension of the solvent must be minimized; for this purpose, a process of replacing water with high surface tension with a solvent having low surface tension is necessary.

[0155] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the solvent that can be mixed with the gelled silica gel as a replacement solvent can be a hydrophilic polar organic solvent, specifically, an alcohol. The alcohol can specifically be: a monohydric alcohol, such as methanol, ethanol, isopropanol, and butanol; or a polyhydric alcohol, such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, and sorbitol, and any one of them or a mixture of two or more of them can be used. Wherein, when considering its miscibility with water and hydrophobic aerogels, the alcohol can be a monohydric alcohol having 1 to 6 carbon atoms, such as methanol, ethanol, isopropanol, and butanol.

[0156] In a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, a drying step for manufacturing aerogel felt from a wet aerogel felt composite material may be performed.

[0157] In a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, the drying step can be carried out by a process of removing solvent while maintaining the pore structure of the aged gel, and the drying step can be carried out by a supercritical drying process or an atmospheric pressure drying process.

[0158] In a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, a supercritical drying process can be carried out using supercritical carbon dioxide. Carbon dioxide (CO2) is gaseous at room temperature and atmospheric pressure. However, when the temperature and pressure exceed predetermined temperature and pressure limits known as the supercritical point, no evaporation process occurs, causing carbon dioxide to become a critical state in which it is indistinguishable from a gas. Carbon dioxide in the critical state is called supercritical carbon dioxide. Supercritical carbon dioxide has a molecular density close to that of a liquid, yet it has a low viscosity, thus exhibiting properties close to those of a gas. Therefore, supercritical carbon dioxide has a high diffusion rate and high thermal conductivity, resulting in high drying efficiency and a shorter drying process time.

[0159] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, a supercritical drying process is performed involving a solvent replacement process, wherein an aged wet aerogel felt is placed in a supercritical drying reactor, and then filled with liquid CO2, which then replaces the alcohol solvent inside the wet aerogel. Subsequently, the temperature is increased to 40°C to 70°C at a predetermined heating rate, specifically 0.1°C / min to 1°C / min, and the pressure is maintained at a pressure greater than that required for carbon dioxide to become supercritical, specifically 100 bar to 150 bar, to maintain the carbon dioxide in the supercritical state for a predetermined amount of time, specifically 20 minutes to 1 hour. Typically, carbon dioxide becomes supercritical at a temperature of 31°C and a pressure of 73.8 bar. The carbon dioxide is maintained at the predetermined temperature and pressure to remain in the supercritical state for 2 hours to 12 hours, more specifically 2 hours to 6 hours. After this, the pressure is typically reduced to end the supercritical drying process, thereby manufacturing the aerogel felt.

[0160] In addition, in a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, the atmospheric pressure drying process can be carried out according to conventional methods, such as hot air drying and near-infrared drying at a temperature of 70°C to 200°C and an atmospheric pressure (1 ± 0.3 atm).

[0161] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, as a result of the above-described drying process, a felt comprising a porous aerogel having nanoscale pores can be manufactured. Specifically, the silica aerogel according to an embodiment of the present invention has excellent physical properties, particularly low density and high porosity, as well as high hydrophobicity, and the felt comprising it containing silica aerogel has excellent mechanical flexibility and low thermal conductivity.

[0162] In addition, in a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, a compression process for controlling the thickness and making the internal structure and surface shape of the felt uniform, a molding process for having a suitable shape or form according to the application, or a lamination process for laminating individual functional layers may be performed before or after the drying process.

[0163] The present invention provides an apparatus for manufacturing aerogel felt, the apparatus being used to implement a second aspect of a method for manufacturing aerogel felt according to an embodiment of the present invention.

[0164] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, such as Figure 1As shown, the apparatus for manufacturing the aerogel felt includes: a spool 100 on which a felt is wound; a body 200 having a gelation tank 210 for receiving the spool 100; a drive element 300 for rotating the spool 100 received in the gelation tank 210; a catalytic sol supply element 400 for injecting catalytic sol into the gelation tank 210; an aging element (not shown) for injecting an aging solution into the gelation tank 210; and a drying element (not shown) for drying the felt by raising the temperature of the gelation tank 210. Here, felt can refer to a substrate for felting before the introduction of catalytic sol, a substrate for felting impregnated with catalytic sol, and / or a wet gel felt after gelation, and can be appropriately understood according to the state of the substrate for felting in each step.

[0165] In a second aspect of a method for manufacturing an aerogel felt according to an embodiment of the invention, the spool is used to wind the felt in a roll and includes a winding rod on which the felt is wound in a roll, and a support plate connected to each end of the winding rod and supporting the sides of the felt wound on the winding rod.

[0166] In a second aspect of a method for manufacturing an aerogel felt according to an embodiment of the invention, the winding rod has a cylindrical shape having a hollow portion extending through the length direction, and a sheet-shaped felt is wound in a roll around its outer peripheral surface.

[0167] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the outer surface of the felt wound on a winding rod allows the catalytic sol to be rapidly impregnated therein, thereby achieving stable gelation. However, there is a problem that it takes a long time for the sol to impregnate the interior of the felt. To prevent the above problem, the outer peripheral surface of the winding rod has a plurality of connection holes that are connected to the hollow core.

[0168] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the winding rod has a hollow space formed therein to allow the introduction of a catalytic sol injected into a gelling tank, and has a plurality of connecting holes to allow the catalytic sol introduced into the hollow space to be discharged to the outside of the winding rod and to impregnate the interior of the felt wound on the winding rod. Therefore, the catalytic sol impregnates both the outside and inside of the felt and gels simultaneously. Thus, the gelling time required for the felt can be greatly shortened, thereby allowing the entire felt to gel uniformly.

[0169] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, a plurality of connecting holes have a diameter of 3 mm to 5 mm, and the holes are formed at regular intervals on the outer peripheral surface of the winding rod. Therefore, the catalytic sol can be uniformly supplied to the entire felt wound on the outer peripheral surface of the winding rod, thereby allowing the entire interior of the felt to be uniformly gelled.

[0170] In a second aspect of a method for manufacturing an aerogel felt according to an embodiment of the invention, the support plate is used to provide support so that the felt wound on the winding rod is not irregularly wound, and has a disc shape. The support plate is connected to the respective ends of the winding rod and supports the sides of the felt wound on the winding rod.

[0171] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the support plate has a fastening groove for connection with the end of a winding rod, and a fastening hole formed on the bottom surface of the fastening groove. That is, the support plate can be connected to the end of the winding rod through the fastening groove.

[0172] In a second aspect of a method for manufacturing an aerogel felt according to an embodiment of the present invention, the support plate has a plurality of openings, and the plurality of openings allow catalytic sol to be introduced into the sides of the felt wound on the winding rod, so that the sides of the felt can be stably gelled.

[0173] In a second aspect of a method for manufacturing an aerogel felt according to an embodiment of the present invention, the roll includes a winding rod and a support plate, so that the felt can be wound in a roll.

[0174] In a second aspect of a method for manufacturing an aerogel felt according to an embodiment of the present invention, the body is a place for mounting a gelling tank that accommodates a roll, and includes the gelling tank and a first mounting element 220 for mounting the gelling tank.

[0175] In a second aspect of a method for manufacturing aerogel felt according to an embodiment of the present invention, the gelling tank is used to gelleave the felt contained in a roll, and includes a gelling chamber disposed therein and containing the roll, an outlet disposed at its lower external end and connected to the gelling chamber, and an inlet disposed at its upper external end and connected to the gelling chamber.

[0176] In a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, specifically, the upper part of the gelation chamber of the gelation tank is opened by a cover, and its lower part has a "U"-shaped cross-sectional shape, which has a curvature corresponding to the felt wound on the winding rod. Therefore, when silica sol is introduced into the gelation chamber, the contact force between the silica sol and the felt increases, and thus, the gelation of the felt can be increased.

[0177] In a second aspect of a method for manufacturing an aerogel felt according to an embodiment of the invention, the gelation tank includes rotating elements disposed on the two walls of the gelation chamber and connected to both ends of a roll to rotate the roll within the gelation chamber.

[0178] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the invention, the rotating element is rotatably mounted in through holes formed on both walls of the gelation chamber, and the end of the roll housed in the gelation chamber is mounted in a power-transmitting manner.

[0179] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, a linear coupling protrusion is formed on one surface of the rotating element, and a linear coupling groove coupled to the coupling protrusion is formed at the end of the roll. That is, through the coupling of the coupling protrusion and the coupling groove, the roll can rotate in the same direction when the rotating element rotates. Therefore, the roll can be rotatably mounted inside the gelation tank.

[0180] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the body further includes a second mounting element 230 in which a catalytic sol supply element is mounted. The second mounting element includes: a base member 231; a mounting platform 232 mounted on the upper part of the base member and mounted such that the catalytic sol supply element is located at a position higher than the gelation tank; and a step 233 mounted at one end of the base member.

[0181] In a second aspect of a method for manufacturing an aerogel felt according to an embodiment of the invention, the gelation tank includes a rotating handle that rotates the spool while being coupled to another rotating element disposed in the gelation tank, and the rotating handle can be manually rotated from the outside.

[0182] In a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, an aging element and a drying element are further mounted on the mounting table of the second mounting element.

[0183] In a second aspect of the method for manufacturing aerogel felt according to an embodiment of the present invention, a drive element is used to rotate a spool housed in a gelling tank and is connected to another rotating element disposed in the gelling tank in a power-transmitting manner. That is, when the drive element rotates the rotating element, it can rotate the spool housed in the gelling tank by interlocking with the rotating element.

[0184] In a second aspect of a method for manufacturing aerogel felt according to an embodiment of the invention, the catalytic sol supply element is used to gel the felt by injecting silica sol into a gelation tank to impregnate the felt wound on a spool, and is mounted on a mounting table. The catalytic sol supply element supplies the catalytic sol to the gelation chamber through the inlet of the gelation tank.

[0185] In a second aspect of a method for manufacturing aerogel felt according to an embodiment of the present invention, an aging element is used to age the felt wound on a spool by injecting an aging solution into a gelation tank, and is mounted on a mounting table. The aging element supplies the aging solution to the gelation chamber through the inlet of the gelation tank.

[0186] In a second aspect of a method for manufacturing aerogel felt according to an embodiment of the invention, a drying element is used to dry the felt wound on a spool by supplying hot air at a high temperature to a gelation tank, and is mounted on a mounting table. The drying element dries the felt contained in the gelation tank by raising the temperature of the gelation tank.

[0187] Therefore, the aerogel felt manufacturing apparatus of the second aspect of the aerogel felt manufacturing method according to one embodiment of the present invention can greatly shorten the manufacturing time of aerogel felt and greatly improve the productivity of aerogel felt, thereby enabling large-scale production of aerogel felt.

[0188] Specifically, according to one embodiment of the invention, the aerogel felt manufacturing apparatus of the second aspect of the method for manufacturing aerogel felt can induce stable gelation by rotating the felt, regardless of the thickness and length of the felt, and because the spool rotates, the entire felt wound on the spool can be gelled uniformly. Furthermore, since only the spool rotates and the gelation tank does not rotate, there is no limitation on the shape of the gelation tank. Moreover, since the gelation chamber in the gelation tank is formed with a "U"-shaped cross-sectional shape, the felt wound on the spool can be gelled more effectively.

[0189] Furthermore, in a second aspect of a method for manufacturing an aerogel felt according to an embodiment of the present invention, the manufacturing apparatus for the aerogel felt includes a spool on which the felt is wound, wherein the spool may include a winding rod and a support plate. Here, the outer peripheral surface of the winding rod may include a retaining clip, in which a winding starting point is inserted and fixed.

[0190] In a second aspect of the method for manufacturing an aerogel felt according to an embodiment of the present invention, the retaining clip has a pin shape with elastic restoring force, and one end of it is fixed to the outer peripheral surface of the winding rod, while the other end is elastically supported on the outer peripheral surface of the winding rod. Therefore, when the starting point of the felt is inserted between the other end of the retaining clip and the winding rod, the felt can be fixed to the starting point of the winding rod by the elasticity of the retaining clip, thereby allowing the felt to be easily wound onto the outer peripheral surface of the winding rod.

[0191] Example

[0192] The embodiments of the present invention will be described in detail below to enable those skilled in the art to readily implement the invention. However, the present invention can be implemented in many different forms and is not limited to the examples set forth herein.

[0193] Example 1

[0194] 31.90 g of pre-hydrolyzed TEOS (silica content = 20 wt%, HTEOS), 31.35 g of ethanol, and 2.8 g of water were added to a reactor and mixed to prepare a silica precursor composition. Meanwhile, 7.77 g of trimethylethoxysilane (TMES) as a hydrophobic agent, 47.28 g of ethanol, 4.22 g of water, and 2.75 g of ammonia (concentration: 30 wt%) as an alkaline catalyst were added to another reactor and mixed to prepare a catalyst composition. In this catalyst composition, based on 1 equivalent of TMES, the total amount of water was 5.2 equivalents, and based on 100 parts by weight of the total sol, the amount of alkaline catalyst was 0.64 parts by weight. The prepared silica precursor composition and catalyst composition were mixed to prepare a silica sol, and the silica sol was impregnated into fibers (glass fiber mat, 10 mm) used as a substrate for a felt. Fiber composites impregnated with silica sol were left to stand at room temperature for 24 hours for gelation, surface modification, and aging. The fabricated silica aerogel felt was placed in a 7.2 L supercritical fluid extractor, and CO2 was injected into it. The temperature inside the extractor was then raised to 70 °C over a period of 1 hour and 20 minutes. At 70 °C and 150 bar, the following cycle was repeated four times: CO2 was injected and evacuated at a rate of 0.5 L / min for 20 minutes, followed by a 20-minute pause in CO2 injection. Ethanol was recovered through the lower end of the extractor during CO2 injection and evacuation. CO2 was then evacuated over a period of 2 hours. After supercritical drying, the aerogel was dried at 150 °C and atmospheric pressure for 1 hour to produce silica aerogel felt.

[0195] Example 2

[0196] <Preparation of Catalytic Sol>

[0197] A silica precursor composition was prepared by mixing methyltriethoxysilane (MTES) and tetraethyl orthosilicate (TEOS) at a molar ratio of 95:5. The silica precursor composition and water were mixed at a molar ratio of 1:10, and ethanol was added at a weight ratio of 1:2 to the silica precursor composition to prepare a silica sol. Hydrochloric acid was added to adjust the pH of the silica sol to below 3 to promote hydrolysis. A 1% (v / v) ammonia-ethanol solution (alkaline catalyst solution) was prepared separately. The silica sol and the alkaline catalyst solution were mixed at a volume ratio of 9:1 to prepare a catalytic sol.

[0198] <Preparation of wet gel mat>

[0199] A spool wound with 10T (10mm) of glass fiber was fixed to the reaction vessel. The catalytic sol prepared above was introduced into the reaction vessel, and the spool wound with glass fiber was rotated to gelatinize. The introduction rate of the catalytic sol was controlled to ensure all catalytic sol was introduced before gelatinization was complete. When the fiber was sufficiently impregnated so that the liquid level in the reaction vessel no longer changed, the drain valve connected to the reaction vessel was opened to recover the remaining sol. After 60 minutes, gelatinization was complete, and then aging was carried out at 60°C for 20 hours. After aging, ethanol was introduced into the reaction vessel at 60°C to displace the solvent.

[0200] <Drying Process>

[0201] The wet aerogel mat is then placed in a conventional oven and dried at 150°C under normal pressure for 2 to 5 hours to completely remove the solvent and moisture, thereby producing a hydrophobic silica aerogel mat.

[0202] Example 3

[0203] In addition to the drying process in Example 2, where the wet aerogel felt was placed in a supercritical extractor and CO2 was injected into it, and the temperature inside the extractor was raised to 50°C for 1 hour to carry out supercritical drying at 50°C and 100 bar, the supercritically dried hydrophobic silica aerogel felt was then dried at atmospheric pressure for 2 hours in an oven at 200°C to completely remove the solvent and moisture, thus manufacturing the hydrophobic silica aerogel felt in the same manner as in Example 2.

[0204] Comparative Example 1

[0205] 31.90 g of pre-hydrolyzed TEOS (HTEOS), 24.41 g of ethanol, and 11.12 g of water were added to a reactor and mixed to prepare a silica precursor composition. Additionally, 60.54 g of ethanol and 0.69 g of ammonia (concentration: 30 wt%) were added to another reactor and mixed to prepare a catalyst composition. The prepared silica precursor composition and catalyst composition were mixed to prepare a silica sol, and the silica sol was impregnated into fibers (glass fiber mat, 10 mm) used as the substrate for the felt. Gelation was induced for 10 minutes to produce a silica wet gel felt. The prepared silica wet gel felt was aged at 50°C for 1 hour using an ammonia (NH3) / ethanol solution (volume ratio 2.2:97.8). Based on the volume of the wet gel mat, 90% by weight of a hexamethyldisilazane (HMDS) / ethanol solution (volume ratio 5:95) was added to the aged silica wet gel mat, and then surface modification was carried out at 70°C for 4 hours.

[0206] The wet aerogel mat is then placed in a conventional oven and dried at 150°C under normal pressure for 2 to 5 hours to completely remove the solvent and moisture, thereby producing a hydrophobic silica aerogel mat.

[0207] Comparative Example 2

[0208] 31.90 g of pre-hydrolyzed TEOS (HTEOS), 24.41 g of ethanol, and 11.12 g of water were added to a reactor and mixed to prepare a silica precursor composition. Additionally, 60.54 g of ethanol and 0.69 g of ammonia (concentration: 30 wt%) were added to another reactor and mixed to prepare a catalyst composition. The prepared silica precursor composition and catalyst composition were mixed to prepare a silica sol, and the silica sol was impregnated into fibers (glass fiber mat, 10 mm) used as the substrate for the felt. Gelation was induced for 10 minutes to produce a silica wet gel felt. The prepared silica wet gel felt was aged at 50°C for 1 hour using an ammonia (NH3) / ethanol solution (volume ratio 2.2:97.8). Based on the volume of the wet gel mat, 90% by weight of a hexamethyldisilazane (HMDS) / ethanol solution (volume ratio 5:95) was added to the aged silica wet gel mat, and then surface modification was carried out at 70°C for 4 hours.

[0209] The silica aerogel mat was then placed in a 7.2L supercritical fluid extractor, and CO2 was injected into it. The temperature inside the extractor was then raised to 70°C over a period of 1 hour and 20 minutes. At 70°C and 150 bar, the following cycle was repeated four times: CO2 was injected and evacuated at a rate of 0.5 L / min for 20 minutes, followed by a period of no CO2 injection for 20 minutes. Ethanol was recovered through the lower end of the extractor during CO2 injection and evacuation. CO2 was then evacuated over a period of 2 hours. After supercritical drying, the aerogel mat was dried at 150°C and atmospheric pressure for 1 hour to produce the silica aerogel mat.

[0210] Comparative Example 3

[0211] 31.90 g of pre-hydrolyzed TEOS (HTEOS), 24.41 g of ethanol, and 11.12 g of water were added to a reactor and mixed to prepare a silica precursor composition. Additionally, 60.54 g of ethanol and 0.69 g of ammonia (concentration: 30 wt%) were added to another reactor and mixed to prepare a catalyst composition. The prepared silica precursor composition and catalyst composition were mixed to prepare a silica sol, and the silica sol was impregnated into fibers (glass fiber mat, 10 mm) used as the substrate for the felt. Gelation was induced for 10 minutes to produce a silica wet gel felt. The prepared silica wet gel felt was aged at 50°C for 1 hour using an ammonia (NH3) / ethanol solution (volume ratio 2.2:97.8).

[0212] The silica aerogel mat was then placed in a 7.2L supercritical fluid extractor, and CO2 was injected into it. The temperature inside the extractor was then raised to 70°C over a period of 1 hour and 20 minutes. At 70°C and 150 bar, the following cycle was repeated four times: CO2 was injected and evacuated at a rate of 0.5 L / min for 20 minutes, followed by a period of no CO2 injection for 20 minutes. Ethanol was recovered through the lower end of the extractor during CO2 injection and evacuation. CO2 was then evacuated over a period of 2 hours. After supercritical drying, the aerogel mat was dried at 150°C and atmospheric pressure for 1 hour to produce the silica aerogel mat.

[0213] Comparative Example 4

[0214] <Preparation of Catalytic Sol>

[0215] Tetraethyl orthosilicate (TEOS) and water were mixed at a molar ratio of 1:10, and ethanol was added at a weight ratio of 1:2 to TEOS to prepare a silica sol. Hydrochloric acid was added to adjust the pH of the silica sol to below 3 to promote hydrolysis. Based on 100 parts by weight of the silica sol, 0.2 parts by weight of TiO2 as a light-blocking agent and 0.2 parts by weight of Ultracarb (LKAB Co., Ltd.) as a flame retardant were mixed and stirred for 30 minutes to prepare a silica sol, and a 1% (v / v) ammonia-ethanol solution (alkaline catalyst solution) was prepared separately. The silica sol and alkaline catalyst solution were mixed at a volume ratio of 9:1 to prepare a catalytic sol.

[0216] <Preparation of wet gel mat>

[0217] A spool wound with 10T (10mm) of glass fiber was fixed to the reaction vessel. The catalytic sol prepared above was introduced into the reaction vessel, and the spool wound with glass fiber was rotated to gelatinize. The introduction rate of the catalytic sol was controlled to ensure all catalytic sol was introduced before gelatinization was complete. When the fiber was sufficiently impregnated so that the liquid level in the reaction vessel no longer changed, the drain valve connected to the reaction vessel was opened to recover the remaining sol. After 30 minutes, when gelatinization was complete, an aging solution was introduced into the reaction vessel to age the sol while the spool was rotated. The aging solution was a 5% (v / v) dilute ammonia ethanol solution, and aging was carried out at 60°C for 20 hours. When aging was complete, the drain valve was opened to recover the aging solution. Subsequently, a surface modification solution was introduced into the reaction vessel to perform surface modification while the spool was rotated, and when this was completed, the surface modification solution was recovered. At this point, the surface modification solution was a 10 vol% methyltetraethoxysilane (MTES) ethanol diluted solution, and an amount was added with the same volume ratio as the wet gel felt composite. Surface modification (hydrophobication) was carried out at room temperature for 8 hours.

[0218] <Drying Process>

[0219] The wet aerogel felt was then placed in a supercritical fluid extractor, and CO2 was injected into it. The temperature inside the extractor was raised to 50°C over 1 hour to perform supercritical drying at 50°C and 100 bar. The supercritically dried hydrophobic silica aerogel felt was then dried at atmospheric pressure for 2 hours in an oven at 200°C to completely remove the solvent and moisture, thus producing the hydrophobic silica aerogel felt.

[0220] Experimental Example

[0221] For the silica aerogel mats manufactured in Examples 1 to 3 and Comparative Examples 1 to 4, the 28-day moisture impregnation rate (MIR-28D), 96-hour moisture impregnation rate (MIR-96H), 15-minute moisture impregnation rate (MIR-15M), dust generation, and room temperature thermal conductivity were measured as follows, and the results are shown in Tables 1 and 2.

[0222] 28-day moisture immersion rate (MIR-28D, weight %): For the silica aerogel mats manufactured in the Examples and Comparative Examples, 100mm × 100mm samples were floated on distilled water at 21 ± 2°C, and a 6.4mm mesh screen was placed on the samples to immerse them 127mm below the water surface. After 28 days, the mesh screen was removed, and the samples were clamped and suspended vertically for 60 ± 5 seconds as they rose to the surface. The weight before and after immersion was then measured to determine the weight gain rate, and the 28-day moisture immersion rate was calculated using Equation 1 below. A lower 28-day moisture immersion rate indicates higher long-term water resistance of the aerogel mat.

[0223] [Equation 1]

[0224] 28-day moisture impregnation rate (MIR-28D, weight %) = {(weight of aerogel mat after 28 days of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water} × 100 96-hour moisture immersion rate (MIR-96H, weight %): For the silica aerogel mats manufactured in the Examples and Comparative Examples, 100mm × 100mm samples were floated on distilled water at 21±2°C, and a 6.4mm mesh screen was placed on the samples to immerse them 127mm below the water surface. After 96 hours, the mesh screen was removed, and the samples were clamped and suspended vertically for 60±5 seconds as they rose to the surface. The weight before and after immersion was then measured to determine the weight gain rate, and the 96-hour moisture immersion rate was calculated using Equation 2 below. A lower 96-hour moisture immersion rate indicates higher mid-term water resistance of the aerogel mat.

[0225] [Equation 2]

[0226] 96-hour moisture impregnation rate (MIR-96H, weight %) = {(weight of aerogel mat after 96 hours of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water} × 100 15-Minute Moisture Impregnation Rate (MIR-15M, weight %): For the silica aerogel mats manufactured in the Examples and Comparative Examples, 100mm × 100mm samples were floated on distilled water at 21 ± 2°C, and a 6.4mm mesh screen was placed on the samples to impregnate them by immersing them 127mm below the water surface. After 15 minutes, the mesh screen was removed, and as the samples rose to the surface, they were clamped and suspended vertically for 60 ± 5 seconds. The weight before and after impregnation was then measured to determine the weight gain rate, and the 15-minute moisture impregnation rate was calculated using Equation 3 below. A lower 15-minute moisture impregnation rate indicates higher short-term water resistance of the aerogel mat.

[0227] [Equation 3]

[0228] 15-minute moisture impregnation rate (MIR-15M, weight %) = {(weight of aerogel mat after 15 minutes of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water} × 100 Dust generation (wt%): For the silica aerogel mats manufactured in the Examples and Comparative Examples, 12mm × 12mm samples were vibrated for 6 hours at 18Hz / 6mm. The weight before and after vibration was then measured to determine the weight loss rate, and dust generation was calculated using Equation 10 below. Lower dust generation indicates better constructability.

[0229] [Equation 10]

[0230] Dust generation (by weight %) = {(Weight of aerogel mat before vibration - Weight of aerogel mat after vibration at 18Hz / 6mm) / Weight of aerogel mat before vibration} × 100 Room temperature thermal conductivity (mW / mK): Samples with dimensions of 30 cm × 30 cm were prepared for the silica aerogel mats manufactured in the Examples and Comparative Examples, respectively. The room temperature (23 ± 5 °C) thermal conductivity of each sample was measured using an HFM 436 Lambda apparatus from NETZSCH Co., Ltd.

[0231] [Table 1]

[0232] [Table 2]

[0233] As shown in Tables 1 and 2, it can be confirmed that Example 1, carried out according to the first aspect of the method for manufacturing aerogel felt according to the present invention, exhibits excellent short-term, medium-term, and long-term water resistance. Furthermore, it can be confirmed that Examples 2 to 3, carried out according to the second aspect of the method for manufacturing aerogel felt according to the present invention, exhibit excellent short-term, medium-term, and long-term water resistance, regardless of drying conditions. This is due to the fact that hydrophobic groups are uniformly introduced onto both the outermost surface and the inner surface of the aerogel in the aerogel felt manufactured according to the present invention.

[0234] In addition, according to Embodiments 1 to 3 of the present invention, the amount of dust generated is suppressed and the thermal conductivity at room temperature is excellent.

[0235] Conversely, unlike the first and second aspects of the method for manufacturing the aerogel felt of the present invention, Comparative Example 1, which only introduces a silica precursor during the preparation of silica sol and performs surface modification by a separate surface modification step, exhibits poor long-term, short-term, and medium-term water resistance. Furthermore, compared to the examples, it can be confirmed that its dust generation and thermal conductivity are increased.

[0236] Furthermore, it can be confirmed that, compared to Comparative Example 1, Comparative Example 2, which underwent supercritical drying under different drying conditions, exhibited improved short-term water resistance, but its long-term water resistance was not improved. This is due to the fact that even with the additional surface modification step, a sufficient amount of surface modifier was not introduced into the aerogel. Therefore, regardless of the drying conditions, when the aerogel is exposed to moisture for an extended period, moisture eventually penetrates into the interior of the aerogel, and moisture adsorption occurs due to the hydrogen bonds between the hydroxyl groups present on the surface inside the aerogel and the moisture.

[0237] Furthermore, unlike the first and second aspects of the method for manufacturing aerogel felt of the present invention, in Comparative Example 3, where only a silica precursor is introduced during the preparation of silica sol and no separate surface modification step is performed, the aerogel felt itself is hydrophilic. Therefore, water is impregnated in it in a very large amount, making it impossible to measure the water impregnation rate. It can also be confirmed that the thermal conductivity of Comparative Example 3 is increased compared to the examples.

[0238] Furthermore, in Comparative Example 4, where the silicate containing hydrophobic groups in the second aspect of the method for manufacturing aerogel felt according to the present invention is not included in the silica precursor composition but is used as a surface modifier in the surface modification step in the same amount, the surface modifier cannot function sufficiently as a hydrophobic agent, and a sufficient amount of surface modifier is not introduced into the aerogel. Therefore, it can be confirmed that the short-term waterproofing, medium-term waterproofing and long-term waterproofing of Comparative Example 4 are all poor.

[0239] The above results confirm that the aerogel felt according to the present invention has excellent long-term waterproof properties, and therefore can maintain its thermal insulation properties even under harsh conditions that would cause long-term exposure to moisture.

[0240] The foregoing description of the invention has been given for illustrative purposes. Those skilled in the art will understand that various changes in form and detail may be made without departing from the spirit and scope of the invention. Therefore, it should be understood that the above embodiments are exemplary in all respects and not restrictive.

Claims

1. An aerogel mat, wherein the 28-day moisture impregnation rate (MIR-28D) calculated by Equation 1 below is less than 100% by weight: [Equation 1] 28-day moisture impregnation rate (MIR-28D, weight %) = {(weight of aerogel mat after 28 days of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water} × 100.

2. The aerogel felt according to claim 1, wherein, The 28-day moisture immersion rate (MIR-28D) calculated using Equation 1 above and the 15-minute moisture immersion rate (MIR-15M) calculated using Equation 3 below satisfy Equation 4 below: [Equation 3] 15-minute moisture impregnation rate (MIR-15M, weight %) = {(weight of aerogel mat after 15 minutes of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water} × 100 [Equation 4] (MIR-28D)-(MIR-15M)≤100.

3. The aerogel felt according to claim 1, wherein, The 28-day moisture immersion rate (MIR-28D) calculated using Equation 1 above and the 15-minute moisture immersion rate (MIR-15M) calculated using Equation 3 below satisfy Equation 5 below: [Equation 3] 15-minute moisture impregnation rate (MIR-15M, weight %) = {(weight of aerogel mat after 15 minutes of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water} × 100 [Equation 5] 1≤(MIR-28D)-(MIR-15M)≤90.

4. The aerogel felt according to claim 1, wherein, The aerogel felt has a 28-day moisture impregnation rate (MIR-28D) of less than 70% by weight, calculated using Equation 1 above.

5. The aerogel felt according to claim 1, wherein, The aerogel mat has a 15-minute moisture impregnation rate (MIR-15M) of less than 20% by weight, calculated using Equation 3 below. [Equation 3] 15-minute moisture impregnation rate (MIR-15M, weight%) = {(weight of aerogel mat after 15 minutes of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water} × 100.

6. The aerogel felt according to claim 1, wherein, The aerogel mat has a 96-hour moisture impregnation rate (MIR-96H) of less than 50% by weight, calculated using Equation 2 below. [Equation 2] 96-hour moisture impregnation rate (MIR-96H, weight%) = {(weight of aerogel mat after 96 hours of impregnation in distilled water at 21±2℃ - weight of aerogel mat before impregnation in distilled water) / weight of aerogel mat before impregnation in distilled water}×100.

7. The aerogel felt according to claim 1, wherein, The dust generation of the aerogel felt, calculated using Equation 10 below, is less than 3.0% by weight. [Equation 10] Dust generation (weight %) = {(weight of aerogel mat before vibration - weight of aerogel mat after vibration at 18Hz / 6mm) / weight of aerogel mat before vibration} × 100.

8. The aerogel felt according to claim 1, wherein, The thermal conductivity of the aerogel felt at room temperature (23±5℃) is below 30.0 mW / mK.

9. The aerogel felt according to claim 1, wherein, The aerogel felt includes an aerogel and a substrate for the felt, wherein the aerogel is formed inside and on the surface of the substrate for the felt.

10. The aerogel felt according to claim 9, wherein, The aerogel contains hydrophobic groups on its internal surface.

Citation Information

Patent Citations

  • Manufacturing method of hydropobic silica aerogel powder with insulating performance

    KR1020120070948A

  • Manufacturing unit of panel for noise lowering

    KR1020190109158A

  • Yul-lan comprising mealworm having enhanced amino acids contents and manufacturing method thereof

    KR1020190121123A

  • Electronic component

    KR1020190121147A

  • Electronic opening and closing device for glove box

    KR1020200084763A